Terahertz Spectroscopy for Non-Destructive Solid-State Investigation of Norfloxacin in Paper Tablets after Wet Granulation - Lara Heidrich; Ayat Abdelkader; Jan Ornik; Enrique Castro-Camus; Cornelia M. Keck; Martin Koch (MDPI AG, 2023)
(1) Background: Amorphous drug systems are an intensively studied approach to overcome the insufficient bioavailability of poorly soluble drugs. Here, paper tablets were studied, which were made from cellulose-based paper matrices loaded with norfloxacin. Moreover, wet granulation was introduced as an additional processing step for improving the flowability of the solids, which is necessary when considering production on an industrial scale. (2) Methods: The possible impact of the wet granulation on the crystallinity of norfloxacin was studied by examining granulated and non-granulated samples. Crystallinity investigations were performed using X-ray powder diffraction (XRD) and terahertz time-domain spectroscopy (THz TDS). (3) Results: THz TDS allowed for a more straightforward crystallinity assessment than XRD. Moreover, using THz TDS, it was possible to detect minor changes in the crystallinity of the API after the granulation, whereas this was not possible with the XRD analysis. (4) Conclusions: THz TDS results indicate a partial crystallization of norfloxacin due to the wet granulation. Depending on the formulation, THz TDS can serve as a beneficial and advantageous tool to determine the crystallinity of an API.